Ventilator associated pneumonia and infection control - Alp Emine; Voss Andreas (BMC, 2006)
Abstract Ventilator associated pneumonia (VAP) is the leading cause of morbidity and mortality in intensive care units. The incidence of VAP varies from 7% to 70% in different studies and the mortality rates are 20-75% according to the study population. Aspiration of colonized pathogenic microorganisms on the oropharynx and gastrointestinal tract is the main route for the development of VAP. On the other hand, the major risk factor for VAP is intubation and the duration of mechanical ventilation. Diagnosis remains difficult, and studies showed the importance of early initiation of appropriate antibiotic for prognosis. VAP causes extra length of stay in hospital and intensive care units and increases hospital cost. Consequently, infection control policies are more rational and will save money.